Intraoral lipoma: Report of 3 cases - RamanPreet Kaur; Shikha Kler; Amandeep Bhullar (Wolters Kluwer Medknow Publications, 2011)
Lipoma, a benign tumor of adipose tissue is one of the most common benign neoplasms of the body. However, its occurrence in oral cavity is very rare. It accounts for 1 to 4% of benign neoplasms of mouth affecting predominantly the buccal mucosa, floor of mouth and tongue. We report three cases of intraoral lipoma, two in buccal mucosa and one in labial mucosa. An excisional biopsy was performed and histopathological examination revealed proliferation of mature adipocytes arranged in lobules and separated by fibrous septa. After 3 years follow up, the patients showed no signs of recurrence.